The caregivers' knowledge on epilepsy and its relationship with stress levels - Lee, Khuan; Abdul Rashid, Nor’ain; Iskan, Norazlin (Asia Pacific Higher Learning, 2024)
Background: Eighty percent of 50 million people who live in economically underdeveloped and developing countries tend to have epilepsy, and more than 50 million people worldwide suffer from this condition. Objective: To determine the levels of knowledge about epilepsy among carers and the relationship this has with their stress levels. Methods: A cross-sectional study design was employed using probability systematic sampling. All the data obtained were analysed using the Statistical Package for Social Sciences (SPSS) version 22. Results: In total, 308 respondents participated in this study. A significant association was found between carers' knowledge levels and stress levels. A significant association was identified between educational level, monthly income, and level of knowledge. However, the results reveal no significant association between carer knowledge and the socio-demographic characteristics of age, gender, and religion. Similarly, no significant association was identified between socio-demographic characteristics and stress levels. Conclusion: This study revealed that most carers who have family members with epilepsy experience moderate levels of stress, even though they have high levels of knowledge. Therefore, stress levels among carers can be reduced by implementing health education related to stress management. Application to practice: Having good knowledge on epilepsy and good social support will reduce stress levels among carers